A case study the expansion of foreign bank in Malaysia: a focus on Standard Chartered / Norfadilah Mohd Rosli - Mohd Rosli, Norfadilah (Faculty of Business and Management, 2010)
The banking industry in Malaysia has been stronger and this report is focused on the development of foreign bank expansion of their market into Malaysia’s banking industries which currently already plenty of foreign bank. Malaysia is a developing country and many investors want to invest in Malaysia. The main objectives of this report, is to analyze the features of Standard Chartered expand their market into Malaysia. Data are collected through key employee of Standard Chartered within its branch and products development personnel. The report also utilizes other research made in the past as its references and data obtain mostly from the central bank of Malaysia, Bank Negara Malaysia as the main evidence and sources.